Intensi Pemilihan Wisata Berkelanjutan di Pulau Belitung: Pengetahuan Pariwisata Sebagai Variabel Moderasi - Kusumah, Echo Perdana; Kusnendi, Kusnendi; Sari, Maya (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
Purpose of this study is to predict the intentions of tourists to choose sustainable tourism destinations based on travel motivation, destination image, and word of mouth (WoM). Destination image factor is moderated by the knowledge factor. Survey targets domestic and international tourists who have visited or planned to travel at least one tourist destination around Belitung Island using the convenience sampling method. A total of 250 online questionnaires were distributed to tourists in popular tourism destinations on the island of Belitung and analyzed using the Smart PLS application. Findings of this study prove that all factors positively influence tourist intentions to choose sustainable tourism destinations. Furthermore, this research proves that tourism knowledge cannot moderate image of destination in intention of tourists to choose sustainable tourism destinations. Belitung Island is one of the main islands in Bangka Belitung Province which is developing tourism potential, especially in marine tourism. Stakeholders related to tourism on Belitung Island must find ways to encourage knowledge sharing among all interested parties and also outside their direct influence, namely information owned by tourists.